A quarter century of TOMS total column ozone measurements over Brazil - Silva, A.A. (Journal of atmospheric and solar-terrestrial physics, 2007)
The Earth's atmosphere has been probed since 1978 by the total ozone mapping spectrometer (TOMS) experiment. In polar orbits around the Earth, Nimbus 7, Meteor 3, and Earth Probe satellites have carried TOMS to measure the backscattered solar ultraviolet radiation, which is processed by Version 8 TOMS algorithm for the retrieval of column ozone values. These TOMS data and their behavior are reported and investigated in this work for some sites in the equatorial and tropical zones of Brazil. Comparison with measurements from Brewer and Dobson spectrophotometers in some cases is provided. An average difference as low as 1.5% between TOMS and Brewer measurements was obtained. In addition, more than two decades of TOMS monthly average column ozone measurements were applied to the calculation of ozone trends. Although small and in general negative, these trends were statistically significant for all sites in the winter season.